Adding cationic guar gum after collector: A novel investigation in flotation separation of galena from sphalerite. (1st October 2020) - Tan, Xin; Zhu, Yangge; Sun, Chuanyao; Zhang, Xingrong; Su, Jianfang
Graphical abstract: Highlights: Galena and sphalerite floated well using diethyldithiocarbamate (DTC) as collector. Cationic guar gum (CGG) exhibited selective depressant effect on sphalerite. Only adding CGG after DTC could realize the separation of galena from sphalerite. Addition order of CGG and DTC could lead to remarkable adsorption difference. Abstract: In this study, the effect of cationic guar gum in the flotation separation of galena from sphalerite when diethyldithiocarbamate acted as galena collector was investigated, mainly through flotation tests and ToF-SIMS analysis. The flotation results showed that the cationic guar gum could selectively depress the sphalerite flotation and enhance the preferential flotation of galena only when it was added after collector diethyldithiocarbamate. The ToF-SIMS analysis found that addition of cationic guar gum after diethyldithiocarbamate exhibited no effect on the collector adsorption on galena surface but could selectively inhibit the collector coverage on sphalerite surface, and further result in the floatability difference.